Respostas
respondido por:
54
é um sistema ?
x - y = 6
x + y = -7
-------------
(x+x) + (-y+y) = 6-7
2x = -1
x = -1/2
x - y = 6
-1/2 - y = 6
-y = 6 + 1/2
-y = 6,5
y = -6,5
x - y = 6
x + y = -7
-------------
(x+x) + (-y+y) = 6-7
2x = -1
x = -1/2
x - y = 6
-1/2 - y = 6
-y = 6 + 1/2
-y = 6,5
y = -6,5
respondido por:
19
x-y=6
x+y=-7
isolando o x
x= 6+y
agora subsituindo na segunda equação
6+y+y=-7
2y=-7-6
2y= -13
y= -13/2
agora voltando na primeira e substituindo
x= 6 -13/2
2x= 12-13
2x= -1
x= -1/2
x+y=-7
isolando o x
x= 6+y
agora subsituindo na segunda equação
6+y+y=-7
2y=-7-6
2y= -13
y= -13/2
agora voltando na primeira e substituindo
x= 6 -13/2
2x= 12-13
2x= -1
x= -1/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás